Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa (SSRN Electronic Journal)
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.

Are we on track with sustainability literacy? - Hahn, Rüdiger; Reimsbach, Daniel (Journal of Global Responsibility)
Purpose – In this viewpoint, the authors aim to discuss sustainability issues in university education. Balancing what we call the “Accounting View” and the “Sustainability View”, the authors illuminate the status of value relevance of sustainability information and question the depth of business students' processing of this information. Design/methodology/approach – The discussion was triggered by an experimental study on sustainability disclosure which revealed interesting findings related to the participating students' prior sustainability and accounting coursework. The authors start the viewpoint from these findings and contrast them with existing views on sustainability and accounting (education). Findings – The amount of accounting coursework was positively related to the probability of including sustainability information in future stock value estimates, whereas this applied only marginally to sustainability coursework. However, students with more sophisticated sustainability knowledge seemed to scrutinize the given sustainability information more deeply, while students with “pure” accounting knowledge seemed more willing to simply accept the information. Practical implications – The authors argue for advancements in the curriculum for business students that foster critical thinking and might prevent students (and thus potential future managers) from using sustainability information superficially. The authors caution against regarding sustainability issues as an “add-on” to existing courses and curricula and call for a combination of integrating sustainability issues in (core) business courses and offering standalone courses on sustainability management or CSR. Originality/value – Triggered by findings from an experimental study, the authors contrast different opinions on sustainability education of business students and offer a new viewpoint on the (supposed) value relevance of sustainability information for future business leaders.
Keywords: Business and International Management

Modeling sequential R&D investments: a binomial compound option approach - Hauschild, Bastian; Reimsbach, Daniel (Business Research)
Abstract In this paper, we propose a binomial approach to modeling sequential R&D investments. More specifically, we present a compound real options approach, simplifying the existing valuation methodology. Based upon the same set of assumptions as prior models, we show that the number of computational steps for valuing any compound option can be reduced to a single step. We demonstrate the applicability of our approach using the real-world example of valuing a new drug application. Overall, our work provides a heuristic framework for fostering the adoption of binomial compound option valuation techniques in R&D management.
Keywords: Business; Management and Accounting (miscellaneous)

Zielorientiertes Management von Logistikdienstleistungen in Netzwerken kooperierender Unternehmen - Puls, Christoph

Integrierte Lagerstandort- und -kapazitätsplanung als Gegenstand der strategischen Logistk - Ortgiese, Malte

Zur Attraktivität von Advance Tax Rulings (ATRs) und Advance Pricing Agreements (APAs) für Investoren und Steuerbehörden: The Attractiveness of Advance Tax Rulings (ATRs) and Advance Pricing Agreements(APAs) for Investors and Tax Authorities, Synopse zur Dissertation - Kortebusch, Pia

Operative Handlungsempfehlungen für eine kostenorientierte Instandhaltungsplanung - Betz, Stefan (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Innovationsrisikomanagement bei unsicheren Cash-Flow-Prognosen - Betz, Stefan (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Integration von Instandhaltungskosten in das Innovationsrisikomanagement - Betz, Stefan (Jahrbuch für Controlling und Rechnungswesen)

Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik

Determinants of market beta: the impacts of firm-specific accounting figures and market conditions - Schlueter, Tobias; Sievers, Sönke (Review of Quantitative Finance and Accounting (VHB-JOURQUAL 3 Ranking B))
This article examines and extends research on the relation between the capital asset pricing model market beta, accounting risk measures and macroeconomic risk factors. We employ a beta decomposition approach that nests competing models with different business risk proxies and allows to frame cross-model comparison. Because model tests require estimated independent variables resulting in measurement error, we empirically estimate three comparable model specifications with instrumental variable estimators and for the first time provide thorough instrument diagnostics in this setting. Correcting for the heretofore neglected weak instruments problem we find that growth risk (i.e., the risk of firm sales variations that are inconsistent with the market wide trends), is the business risk that explains cross-sectional variations in market beta best.
Keywords: CAPM; Cost of capital; Accounting beta; Intrinsic business risk; Growth risk; Instrumental variables

Mehr Theorie wagen: Eine neue Ausbildung für die Praxis? - Sureth-Sloane, Caren (WiSt - Wirtschaftswissenschaftliches Studium)

Besteuerung und Rechtsformwahl - König, Rolf; Sureth-Sloane, Caren

Vermögensteuer vernichtet Eigenkapital - Maiterth, Ralf; Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

The Impact of Corporate Taxes and Flexibility on Entrepreneurial Decisions with Moral Hazard and Simultaneous Firm and Personal Level Taxation - Meißner, Fabian; Sureth-Sloane, Caren

Die Reichensteuer gefährdet Arbeitsplätze - Sureth-Sloane, Caren (Cicero Online)

Investment distortions and the value of the government's tax claim - Kreutzmann, Daniel; Sievers, Sönke; Mueller, Christian (Applied Financial Economics (VHB-JOURQUAL 3 Ranking C))
This study integrates the government in the context of company valuation. Our framework allows to analyze and to quantify the risk-sharing effects and conflicts of interest between the government and the shareholders when firms follow different financial policies. We provide novel evidence that firms with fixed future levels of debt might invest more than socially desirable. Economically, this happens if the gain in tax-shields is big enough to outweigh the loss in the unlevered firm value. Our findings have implications for the practice of investment subsidy programs provided by the government to avoid fostering investments beyond the socially optimal level.
Keywords: corporate tax claim; company valuation; optimal investment; cost of capital

Extended dividend, cash flow, and residual income valuation models: Accounting for deviations from ideal conditions - Heinrichs, Nicolas; Hess, Dieter; Homburg, Carsten; Lorenz, Michael; Sievers, Sönke (Contemporary Accounting Research (VHB-JOURQUAL 3 Ranking A))
Standard equity valuation approaches (i.e., DDM, RIM, and DCF model) are derived under the assumption of ideal conditions, such as infinite payoffs and clean surplus accounting. Because these conditions are hardly ever met, we extend the standard approaches, based on the fundamental principle of financial statement articulation. The extended models are then tested empirically by employing two sets of forecasts: (1) analyst forecasts provided by Value Line and (2) forecasts generated by cross-sectional regression models. The main result is that our extended models yield considerably smaller valuation errors. Moreover, by construction, identical value estimates are obtained across the extended models. By reestablishing empirical equivalence under non-ideal conditions, our approach provides a benchmark that enables us to quantify the errors resulting from individual deviations from ideal conditions, and thus, to analyze the robustness of the standard approaches. Finally, by providing a level playing field for the different valuation approaches, our findings have implications for other empirical settings, for example, estimating the implied cost of capital.
Keywords: Dividend Discount Model; Residual Income; Discounted Cash Flow; Dirty Surplus; Terminal Value; Valuation Error

Company Valuation and Growth: Theory, Empirical Evidence and Practical Implementation Issues - Sievers, Sönke
Keywords: Unternehmensbewertung; Unternehmenswachstum; Return on Investment Unternehmensbewertung; Investition; Steuervergünstigung

The relevance of financial versus non-financial information for the valuation of venture capital-backed firms - Sievers, Sönke; Mokwa, Christopher F; Keienburg, Georg (European Accounting Review (VHB-JOURQUAL 3 Ranking A))
This study examines the relevance of financial and non-financial information for the valuation of venture capital (VC) investments. Based on a hand-collected data set on venture-backed start-ups in Germany, we investigate the internal due diligence documents of over 200 investment rounds. We document that balance sheet and income statement items capture as much economic content as verifiable non-financial information (e.g. team experience or the number of patents) while controlling for several deal characteristics (e.g. industry, investment round, or yearly VC fund inflows). In addition, we show that valuations based on accounting and non-accounting information yield a level of valuation accuracy that is comparable to that of publicly traded firms. Further analyses show that the industry-specific total asset multiples outperform the popular revenue multiples but lead to significantly less accurate results than those obtained from the more comprehensive valuation models. Overall, our findings might inform researchers and standard-setters of the usefulness of accounting information for investment companies and provide additional evidence to gauge the overall valuation accuracy in VC settings.
Keywords: value relevance; equity valuation; venture capital; human capital; start-ups

Valuing high technology growth firms - Klobucnik, Jan; Sievers, Sönke (Journal of Business Economics (VHB-JOURQUAL 3 Ranking B))
For the valuation of fast growing innovative firms Schwartz and Moon (Financ Anal J 56:62–75, 2000), (Financ Rev 36:7–26, 2001) develop a fundamental valuation model where key parameters follow stochastic processes. While prior research shows promising potential for this model, it has never been tested on a large scale dataset. Thus, guided by economic theory, this paper is the first to design a large-scale applicable implementation on around 30,000 technology firm quarter observations from 1992 to 2009 for the US to assess this model. Evaluating the feasibility and performance of the Schwartz-Moon model reveals that it is comparably accurate to the traditional sales multiple with key advantages in valuing small and non-listed firms. Most importantly, however, the model is able to indicate severe market over- or undervaluation from a fundamental perspective. We demonstrate that a trading strategy based on our implementation has significant investment value. Consequently, the model seems suitable for detecting misvaluations as the dot-com bubble.
Keywords: Schwartz-Moon model; Market mispricing; Empirical test; Company valuation; Trading strategy

Die erfolgreiche Bindung des Sparers an die Bank - Sievers, Sönke; Schlüter, Tobias; Hartmann-Wendels, Thomas (Börsen-Zeitung)

Wie Banken Kostenvorteile weitergeben - Sievers, Sönke; Hartmann-Wendels, Thomas; Busch, Ramona; Schlüter, Tobias (Börsen-Zeitung)

Der Einfluss von Steuern auf Investitionsentscheidungen bei Unsicherheit - Sureth, Caren

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

The light and dark side of TARP - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Banking and Finance)
Employing four event dates of the U.S. “Troubled Asset Relief Program” (TARP) this paper empirically investigates the impact of the first announcement of TARP (September 19, 2008), the announcement of revised TARP (October 14, 2008), respective capital infusions under TARP-CPP and capital repayments on changes in shareholder value and risk exposure of 125 supported U.S. banks as perceived by the capital market through share price reactions for an entire sample period from September 19, 2008 to June 16, 2010. Our analysis reveals a light and a dark side of TARP. While announcements as well as capital repayments may restore market confidence and financial stability, equity capital injections to banks are observed to be a severe impediment to an increase in bank shareholder value and financial soundness.
Keywords: Financial crisis; TARP; Market efficiency; Event study

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Does Mandatory IFRS Adoption Improve the Credit Relevance of Accounting Information? - Kosi, Urska; Florou, Annita; Pope, Peter F.

Write-offs and profitability in private firms: Disentangling the impact of tax-minimisation incentives - Kosi, Urska; Valentincic, Aljosa (European Accounting Review)
Private firms are likely to use the financial reporting process more for other objectives, such as tax savings, than for communicating performance. However, observing firms choosing accounting policies for tax-minimisation purposes is not straightforward due to (i) tax and non-tax costs of reporting lower income (ii) accounting policies that result in lower reported income and no tax savings but generate non-tax benefits (iii) preparers' multiple incentives and (iv) econometric issues. We observe a large sample of 20,505 private firms writing off assets in two separate regimes, one that generates tax savings and one that does not. Firms significantly decrease, but continue to use, write-offs after the adverse change in tax treatment of write-offs. The exogenous tax change should not affect other reporting incentives. This allows us to disentangle the tax-minimisation incentive from other (un-observable) incentives, including debt contracting, dividends and employee relations that contribute to the observed anomalous positive relationship between write-offs and profitability. We show that for private firms (i) obtaining tax savings is important overall (ii) non-tax costs and benefits are probably also important and (iii) earnings informativeness for future cash flows increases after the adverse tax legislation change.

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Sooner or Later? – Paradoxical Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (European Accounting Review)

Advance Pricing Agreements (APAs) als Instrument zur Vermeidung von Verrechnungspreiskonflikten – eine kritische Betrachtung - Vollert, Pia; Eikel, Carolin; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Pro forma earnings disclosure: the effects of non-GAAP earnings and earnings-before on investors’ information processing - Reimsbach, Daniel (Journal of Business Economics)
Keywords: Economics and Econometrics; Business and International Management

The Effects of Negative Incidents in Sustainability Reporting on Investors’ Judgments–an Experimental Study of Third‐party Versus Self‐disclosure in the Realm of Sustainable Development - Reimsbach, Daniel; Hahn, Rüdiger (Business Strategy and the Environment)
ABSTRACT This study examines how the disclosure of negative sustainability‐related incidents affects the investment‐related judgments of decision‐makers. Participants in a sequential 2 × 2 between‐subjects experiment first received a company's financial information before viewing additional sustainability information (by the company and by a non‐governmental organization (NGO); with and without negative disclosure). Results indicate that self‐reporting of negative incidents does not affect decision‐makers’ stock price estimates and investment decisions compared with judgments based on financial information only. However, third‐party disclosure of these incidents by a NGO has a negative affect on these investment‐related judgments. Furthermore, the magnitude of the NGO reporting effect depends on whether the company itself simultaneously reports these incidents. Thus, disclosing negative incidents in sustainability reporting could lose some of its apparent stigma. Instead of avoiding negative reporting altogether, managers might use it as a risk mitigation tool in their reporting strategy. The results also emphasize the power of the often‐mentioned ‘watchdog’ function of NGOs acting as stakeholder advocates. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

Einsatz der Risikoanalyse als Instrument des Investitionscontrollings - Koch, Christian (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Kostenorientiertes Management von Logistikdienstleistern - Puls, Christoph (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Integrierte, ökologieorientierte Produktlebenszyklusrechnung - Opitz, Oliver (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Integrierte, ökologieorientierte Produktlebenszyklusrechnung - Faupel, Christian (Industrielles Controlling - Planung, Steuerung und Kontrolle von Beschaffung, Produktion und Logistik)

Entscheidungsorientierte Planung unscharfer Erfolge von KMU in Supply Chains - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Analyse des Bullwhip-Effekts in einer Supply Chain von KMU - Betz, Stefan (Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand)

Entscheidungsprobleme im Supply Chain Management - Quantitative Lösungsansätze für den Mittelstand

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Sievers, Sönke; Mokwa, Christopher Frederik
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

A Tax Paradox for Investment Decisions under Uncertainty - Gries, Thomas; Prior, Ulrich; Sureth-Sloane, Caren (Journal of Public Economic Theory)

Besteuerung von Beteiligungsinvestitionen und Risikoempfindlichkeit – Wie wirkt die Abgeltungssteuer? - Hegemann, Annika

Asymmetric Taxation of Profits and Losses and Its Influence on Investment Timing: Paradoxical Effects of Tax Increases - Mehrmann, Annika; Schneider, Georg; Sureth-Sloane, Caren

Mehr Theorie wagen. Betriebswirtschaftslehre nach Bologna oder Hochschulbildung im Wandel - Sloane, Peter F. E.; Sureth-Sloane, Caren (Wirtschaft und Beruf)

Analytisch und strukturiert denken lernen - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Studium nach Bologna: Theorie oder Praxis – ein Scheinwiderspruch? - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Unternehmensführung und interkulturelle Hochschulbildung. Unternehmensführung in Europa - Interkulturelle Fragen - Sureth-Sloane, Caren (Wirtschaft und Beruf)

Vorwort. Geschichte des VHB und der BWL: Rückblick und Einblicke - Sureth-Sloane, Caren (Der Verband der Hochschullehrer für Betriebswirtschaft, Geschichte des VHB und Geschichten zum VHB)